THE INFLUENCE OF POLITICAL ASPECTS IN LEGAL REFORM: PENGARUH ASPEK POLITIK DALAM PEMBAHARUAN HUKUM - Firmansyah, Ade Arif; Evendia, Malicia (Center for Constitutional and Legislative Studies University of Bandar Lampung, 2023)
This paper aims to see the influence of political aspects in legal reform. By using a conceptual approach, it was found that:In the context of legal reform, political aspects have a significant influence, this can be seen in the formation of the Constitutional Court. The formation of the Constitutional Court was realized because of the political desire to form a state institution that could control the legislative products of the DPR, synchronize it with the 1945 Constitution so that there would be no violations of the constitutional rights of citizens and to maintain the principle of checks and balances between state institutions. The establishment of the Constitutional Court is a form of legal reform in a formal institutional sense. Apart from the context of forming legislation for legal reform, political aspects can also actually influence law enforcement. This can be seen in the handling of protracted corruption cases, as well as the use of a reverse evidence system in corruption cases, making it easier for law enforcers to work. This reverse evidence system is a form of legal reform.